Contribution of the Geodiversity knowledge to social, economic, and environmental health development - Cassio Silva; Edson Farias Mello; Gilberto Dias Calaes; Patricia Duringer Jacques; André Luiz Invernizzi (Journal of the Geological Survey of Brazil)
With the support of this study, based on published information, this article highlights that Geosciences enable the research of methods and perspectives aimed at optimizing the management of natural resource use, aligning them with ecological limitations and incorporating environmental and social variables into the territorial planning process. Geoscientific information, knowledge, and learning establish a foundation for the supply of essential resources and provide technical and scientific support across various sectors and topics of societal interest. These include mining, where knowledge and proper utilization of essential mineral resources are crucial for human survival and quality of life; energy, which relies on petroleum, gas, coal, peat, and other minerals for nuclear energy generation, as well as for renewable energy sources like wind and solar power. Agriculture, which depends on fertilizers, soil remineralizers, conditioners, and a reliable water supply. In the field of public health, geoscientific knowledge helps ensure the quality of water, soil, and air. In urban planning, it guides land-use restrictions or expansion. In housing, the availability of construction materials is essential. In civil defense, geoscientific insights are crucial for managing landslides, floods, earthquakes, subsidence, and erosion. Regarding infrastructure, geosciences support both social (housing, sanitation, education, healthcare) and economic (energy, transportation, communications) developments. Tourism benefits from geoparks and scenic areas, while environmental studies focus on impact assessments, disaster prevention, and the rehabilitation of degraded areas. Moreover, geoscientific knowledge is indispensable for planning across various sectors of the economy, regions, and societal issues. This applies to public institutions, civil society organizations, private companies, and watershed committees, aiding in the formulation of Regional Development Plans, Ecological-Economic Zoning, Territorial Planning, and strategies for the utilization of continental shelves, coastal environments, and accident prevention. We are entirely dependent on the geological characteristics of natural environments, as they provide the raw materials—such as minerals, water, and food—necessary for our survival and socio-economic development. As geoscientific knowledge and understanding of land and environmental suitability and limitations increase, Geodiversity can play a more significant role in shaping public policies related to urban and rural land use, infrastructure, and the sustainable economic exploitation of mineral and water resources, aligning with Municipal Master Plans, State Development Plans, and the National Territorial Planning Strategy.